Students’ Perception of Online Dating: An Exploratory Investigation - Peter Voo Su Kiong; Ismail Maakip; Azizi Yahaya; Balan Rathakrishnan (ResearchGate, 2023)
Online dating offers significant advantages for single people such as it provides an effective and less expansive choice of approach in choosing a date. However, with so many online dating sites there would be pros and cons in choosing and participating in the site. This present study explores an individual’s opinion about online dating among university students. A qualitative research approach was chosen to explore their perception and opinion on online dating. Respondents are required to answer a question by writing a self-report during a structured interview. Then, they were to answer a standard quiz which retrieved from America PEW Research Centre. Data collected were compared to reassure the validity and reliability of the result. Research founds that majority of respondents hold a neutral point of view on online dating. The implication of this study gives some insight into the view and perception of a university student on the aspect of online dating which might be influenced by their upbringing and culture/norms.